THE UTILIZATION OF EDMODO AS LEARNING STRATEGY IN TEACHING WRITING - Alfian, Alfian (Eduscience : Jurnal Ilmu Pendidikan, 2017)
AbstractThe main objective of this present study aimed at investigating utilization of Edmodo to be used as a learning strategy in teaching writing to the tenth grade students of Al-Azhar Bumi Serpong Damai. Both the advantages and disadvantages experienced by the teacher and students while writing Recount and Narrative activities are investigated during four cycles. Classroom action research was used as its basic design. Action research cycles like; (Plan, action, observation, and reflection) is used to get a clear data. As the instrument, the writer used triangulation technique. He did the observation, gave the questionnaire to the students, and did an interview with several students. The result of this research indicates that the utilization of Edmodo in which the process approach used in its activities such as writing for an audience, peer review, self-editing and revising has undoubtedly impacted on the students writing quality. Overall, the tenth grade students of Al-Azhar Bumi Serpong Damai perceive that Edmodo micro-blogging as a useful, reflective and effective writing tool. This study found that students are ready to embrace this tool to be part of their learning environment.  Keywords: edmodo, learning strategy,  teaching writing AbstrakTujuan utama dari penelitian ini adalah untuk menyelidiki pemanfaatan Edmodo untuk digunakan sebagai strategi pembelajaran dalam pengajaran menulis kepada siswa kelas X Al-Azhar Bumi Serpong Damai. Baik kelebihan maupun kekurangan yang dialami oleh guru dan siswa saat kegiatan menulis Recount dan Narrative diselidiki selama empat siklus.           Penelitian tindakan kelas digunakan sebagai desain dasarnya. Siklus penelitian tindakan seperti; (Plan, action, observasi, dan refleksi) digunakan untuk mendapatkan data yang jelas. Sebagai instrumennya, penulis menggunakan teknik triangulasi. Penulis melakukan observasi, memberi kuesioner kepada para siswa, dan melakukan wawancara dengan beberapa siswa. Hasil penelitian ini menunjukkan bahwa pemanfaatan Edmodo dimana pendekatan proses yang digunakan dalam aktivitasnya seperti menulis untuk audiensi, peer review, editing sendiri dan revisi tidak diragukan lagi berdampak pada kualitas penulisan siswa. Secara keseluruhan, siswa kelas X Al-Azhar Bumi Serpong Damai. menganggap bahwa micro-blogging Edmodo sebagai alat tulis yang berguna, reflektif dan efektif. Studi ini menemukan bahwa siswa siap untuk merangkul alat ini untuk menjadi bagian dari lingkungan belajar mereka. Kata Kunci: edmodo, strategi belajar, pengajaran menulis